The Role of The Madrasah Head In Implementing Collaborative Academic Supervision At Min 2 West Bandung - Nailan, Akhmaliah Siti (Fahmina: Jurnal Pendidikan Islam, 2024)
The principal's role as a supervisor is to help improve teacher professionalism and ensure that students' needs are met in the learning process. Through supervision, school principals can improve the quality of learning and ensure that the supervision program carried out provides maximum results. This study aims to explore and analyze the application of collaborative academic supervision carried out by the head of Madrasah Ibtidaiyah Negeri (MIN) 2 West Bandung. Academic supervision is an important aspect in ensuring the quality of education and increasing teacher professionalism. The research method used is descriptive qualitative with a case study approach. Data was collected through in-depth interviews, observation and documentation. The research results show that madrasa heads implement various supervision strategies, including careful supervision planning, systematic implementation of supervision, as well as continuous evaluation and follow-up. Supporting factors in academic supervision include the competency of the madrasa head, teamwork, and support from related educational institutions. However, this research also identified several obstacles, such as limited time, high workload, and lack of resources. The recommendations of this research are the need to increase training and professional development for madrasa heads as well as increase support from the government and educational institutions to optimize academic supervision. It is hoped that this research can contribute to the development of more effective academic supervision practices in madrasah.